Architectural formations in the works of potter Tariq Ibrahim: انعام خليل ابراهيم (Al-Academy, 2021)
Artistic formation is an interconnected system of a group of elements and units interconnected with each other in an interwoven fabric, which in turn will be forms with ideas and contents that the artist is keen to convey to the recipient, the formative building includes various types of visual arts, and architecture is in turn a visual art, built from a group Elements and units that show their aesthetic value during the intersection of their building lines and the systems and models of building their external walls, which may be built with a system of incomes and projections or protrusions and pits in their walls, which creates different areas of shade and light during the fall of the sun's rays on them, so their aesthetic value increases, especially what we see in ancient civil buildings, and not We forget the other complementary elements of construction, such as windows, doors, and their construction patterns, and due to the aesthetics of these architectural forms, they became the inspiration for the artists who added the idea of these shapes to plastic works, especially in contemporary Iraqi ceramics, and the artist Tariq Ibrahim is an Iraqi potter who attracted him and aroused his interest in architectural structures, especially houses in clay. And the old heritage houses have always been attracted by their construction material, which is clay, and based on that, the research problem is possible, and the question arises: Next: What are the architectural formations and how did the potter Tariq Ibrahim employ them in his ceramics? The methodological framework included: the importance of research and the need for it, the goal of research, and spatially defined: Iraq. Chronological formations are defined: 1980-2000, and thematically: Architectural formations in the works of potter Tariq Ibrahim.The theoretical framework contains three topics: The first topic: the concept of training in the plastic arts, the second topic: architecture and art, and the third topic: contemporary Iraqi ceramics and the indicators of the theoretical framework.The research procedures were: the research community, the research method, the research sample, the research tool, and the sample analysis. He concluded with the results and conclusion), including:1. Show the shapes and configurations of cities and homes on the surfaces of hard ceramic works with geometric shapes, as in sample (1) and (2).2. The potter, Tariq Ibrahim, the architectural formations were evident in his ceramic works.The chapter concluded with recommendations and suggestions, and sources and references.